The Reconstruction of Energy Management Law Based on Indonesia Legal System - Sulaiman Sulaiman; Ade Arif Firmansyah (Universitas Lampung, 2018)
Two things become an important part of studies in Indonesian law related to energy management. The first, related to the management of natural resources. Second, the energy sector is also related to other sectors, that is forestry, water resources, marine and fisheries, agriculture and plantations, as well as land. Ideally, all of the energy management law must reflect the state ideology, as natural resources energy must be managed for the greater prosperity of the people. Energy should not be administered arbitrarily because, in addition to the utilization, the existence of natural resources should not be separated from the philosophical orientation of Indonesian legislation, Pancasila, and The 1945 Constitution. However, the reality of energy legislation indicates of the authority competes between sectors and alignments to society which is not optimal. It is due to the legal nature of the energy sector which is liberal and still-exploitation oriented and pro-capitalist. By using a socio-legal approach, this paper describes the reconstruction of law-oriented to the Indonesian legal system in energy management based on Pancasila and the 1945 Constitution as the foundation and soul of the energy sector law. Keywords: Reconstruction of Law, Energy Management, the Indonesian Legal System.